The Insect diversity at some national parks and nature reserves of Vietnam - Thinh, Ta Huy; Tru, Hoang Vu; Du, Tran Thieu; Thai, Pham Hong (Academia Journal of Biology, 2015)
The insect samples were taken in the period of May-July in 2001, 2002 and 2003 from eight sites: the Tamdao, Hoanglien-Sapa, Babe and Catba national parks, the Hangkia-Paco and Muongphang nature reserves (from the Northern part of Vietnam), the Bachma national park (from the Middle part of Vietnam) and the Dambri nature reserve (from the Southern part of Vietnam). Insects were collected by the insect net along the forest routes that are 40 km long in each site. The purpose of the sampling was to collect a sample that was comparable with similar samples taken from other sites. For this purpose, the actual sampling routes were chosen to be typical of the study site so that all major habitat types could be sampled. The sampling included the insects flying and/or staying on ground, on grass and on trees that could to see and to catch, except the social insects. In addition, every 100m walking is also allowed to stay for making ten catches by chance. From eight sites, the authors have collected 201 families of 11 Insect orders: Coleoptera-61 families, Diptera-47, Hymenoptera-25, Homoptera-22, Heteroptera-14, Lepidoptera (Rhopallocera)-9, Orthoptera-10, Phasmatoidea-4, Blattodea-3, Mantodea-3 and Dermaptera-3. The beetles had the highest value of portion as of the species number as well of the individual number (25.5-48.9% and 23.1-57.1%, respectively.) A variety of different indices was used as measures of some attributes of the insect community structure in the samples. These included the total individual number (N), the total species number (S), the total family number (Sfam) and also the Margalef’s index (d), the Pielou’s evennes index (J’), the Simpson dominance index (1 - l’), the Shannon-Wiener diversity index (H’) as well as the Bray-Curtis similarity coefficient (S’jk). The samples, collected from the Tamdao, Muongphang and Dambri sited contained more species that showed more high value of the species richness than the others. However, the formers had low evenness and high dominance so that considered to decrease the diversity (e.g. H’). The incorporation of different measures in these samples tended to conclude that the insect communities at these eight national parts and nature reserves have high degree of diversity; among them, the insect communities at Tamdao, Muongphang  and Dambri had higher value of d and H’ than the others. On other hand, it seems that the insect communities at limestone forest were less rich in comparison with those at the ground one. The study results also have showed a correlation between the species richness and the family level at these eight sites (R= 0.697). The result of a cluster analysis on Insect data at family level based on Bray-Curtis similarities has showed that the family similarity took the value in the range of 57.15-74.33%. The actual dissimilarity between the samples depended on the geographic factor as well as on the forest kind.